Sepsis-Induced Coagulopathy as a Risk for Postoperative Arterial Thrombosis: A Case Report - Swastikasari, Dewi; Permana, Septian Adi (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Venous thromboembolic disease and arterial thrombosis are recognized as common causes of hospital mortality, especially in postoperative patients, those who are immobilized, and individuals with sepsis. Coagulopathy is a significant factor due to the interaction between inflammation and coagulation, stemming from widespread endothelial damage.Case: We report manifestations of sepsis-induced coagulopathy (SIC) in a 64-year-old woman who was treated at the intensive care unit (ICU) of RSUD Dr. Moewardi with peripheral arterial disease. The patient was treated for 20 days in the ICU with a multidisciplinary approach. The patient's clinical outcome was good and planned for follow-up during outpatient care.Discussion: Thrombosis and inflammation are distinct yet closely interconnected physiological processes. In a normal physiological context, the activation of the coagulation system by inflammation is a component of the body's defense mechanism against pathogens, aiming to restrict their spread within the bloodstream. This protective response involves the interaction between innate immune cells and platelets.Conclusion: By gaining a deeper insight into sepsis-associated coagulopathy (microthrombopathy), we can develop effective treatments that specifically target the microthrombotic pathway involved in endothelial damage.